Creation and the Glory of Creatures. (25th March 2013) - Soskice, Janet Martin
Abstract: This article speaks in praise of the dignity of creatures. Arguing for a foundation of the nascent doctrine of creatio ex nihilo in the Psalms and inter‐testamental scriptures, Soskice points to the distinctiveness of the Jewish and Christian understanding of the Creator God, and its revolutionary entrance into the bloodstream of western metaphysics. She argues for a qualification on the over‐emphasis, when speaking of the historical origins of the doctrine, on the creation of matter. Wider principles of divine freedom and transcendence are at work as can be seen in the writings of Philo of Alexandria. The conviction that God is Being itself and the source of all being is the legacy not of 'Greek philosophy' simpliciter, as is often invoked by way of curt dismissal, but the product of Jewish and Christian middle‐platonic readings of the Book of Exodus. It is this elaboration of creatio ex nihilo which underscores the Christian theology of participation in which creatures are not diminished but made gloriously and truly themselves.